A collision-free model on the interaction between pedestrians and cyclists on a shared road. (1st November 2021) - Huang, Chuanli; Hu, Yanghui; Zhang, Sainan; Yang, Longnan; Xia, Long; Zhang, Jun; Song, Weiguo; Lo, Siuming
Abstract: In this study, we aim to propose a collision-free model on the interaction between pedestrians and cyclists on a shared road. First, we design an experiment to investigate the behaviors of pedestrians and cyclists in the interaction process. Three principles are presented for modeling based on the experimental observations, including the perception difference in the bidirectional and unidirectional scenarios, the difference in sensitivity on safety distance of pedestrians and cyclists, and the effect of distance and moving direction on the deceleration and steering behaviors. The model is proposed under the concept of subjective perception and behavioral decision-making. The heuristic of the path decision is that if a pedestrian (cyclist) decides to detour, he/she prefers the shortest route on the premise that a minimum safety distance is kept from the cyclist (pedestrian). The speed adjustment of both pedestrians and cyclists includes two parts: the expected speed determined by the available headway distance, and the deceleration coefficient determined by the distance between the cyclist and the pedestrian for the safety concern. The direction-related parameters are calibrated directly through the trajectories, while the speed-related parameters are calibrated with the cross-entropy method. The microscopic validation implies that the proposed collision-free model can potentially be used to simulate the microscopic interaction between pedestrians and the cyclist. It is also worth noting that the perception uncertainty of pedestrians could generate a big challenge to physical models on simulating the microscopic behaviors of pedestrians when the potential collision comes from the behind. The simulation of the mixed traffic reveals the difference in lane formation phenomena and the consequential conflict intensity between a cyclist and the crowd in bidirectional and unidirectional situations.